Effectiveness of Digital Media Use in Literacy Learning at SDN 2 Wisma Kerta Sidemen, Karangasem - Ni Made Viona Adelia Cahyani; Ni Putu Hikari Tresnayanti; Ni Made Nindi Ambarwati; Ni Nengah Mery Handayani; Ni Putu Mita Ardiyanti; Basilius Redan Werang (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to increase student literacy at SDN 2 Wisma Kerta through the use of digital media. The service process includes identifying needs, teacher training, and implementing digital media in learning. The method used is a participatory approach, involving teachers and students actively at every stage. The service schedule is carried out for three months, starting from June to August 2024, with regular training and evaluation sessions. The results of the service show a significant increase in students' interest and literacy skills. The implication of this service is the importance of integrating digital media in learning to improve the quality of basic education.